Predicting Directions of Changes in Genotype Proportions Between Norovirus Seasons in Japan - Suzuki, Yoshiyuki; Doan, Yen Hai; Kimura, Hirokazu; Shinomiya, Hiroto; Shirabe, Komei; Katayama, Kazuhiko (Frontiers in Microbiology, 2019)
The norovirus forecasting system (NOROCAST) has been developed for predicting directions of changes in genotype proportions between human norovirus (HuNoV) seasons in Japan through modeling herd immunity to structural protein 1 (VP1). Here 404 nearly complete genomic sequences of HuNoV were analyzed to examine whether the performance of NOROCAST could be improved by modeling herd immunity to VP2 and non-structural proteins (NS) in addition to VP1. It was found that the applicability of NOROCAST may be extended by compensating for unavailable sequence data and observed genotype proportions of 0 in each season. Incorporation of herd immunity to VP2 and NS did not appear to improve the performance of NOROCAST, suggesting that VP1 may be a suitable target of vaccines.